Ð•Ð»Ð°ÑÑ‚Ð°Ð·Ð¸ Ð¿Ñ€Ð¸ ÑˆÑ‚ÑƒÑ‡Ð½Ð¾Ð¼Ñƒ Ð³Ñ–Ð¿Ð¾Ð¼ÐµÑ‚Ð°Ð±Ð¾Ð»Ñ–Ð·Ð¼Ñ– Ñƒ Ñ‰ÑƒÑ€Ñ–Ð² - Samokhina, L. M.; Lomako, V. V.; Shilo, A. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The development of artificial hypometabolism in rats contributes to tissue-specific rise in elastase activity, metalloeastase and decreased level of endothelial elastase. These changes are partially normalized in 24 hrs, herewith there was noted the participation of Î±-1-inhibitor of proteinases in suppressing of surplus activity of elastases.